38. POST-INTERVENTION EFFECTIVENESS ASSESSMENT ON THE IMPROVEMENT OF MANAGEMENT COMPETENCY AMONG HEADNURSES AT HOSPITALS AND HEALTH CENTERS WITH INPATIENT BEDS IN TUYEN QUANG PROVINCE IN 2024 (Vietnam Journal of Community Medicine, 2025)
Objectives: To evaluate the change in management capacity of head nurses at hospitals and medical centers with beds in Tuyen Quang province after capacity building and supervision training courses.Method: The study used a pre-post training comparison method on 89 head nurses at 14 hospitals and medical centers with inpatient beds in Tuyen Quang province from November to December 2024.Results: 8/11 criteria on management capacity, 10/13 criteria on human resource management capacity, 7/8 criteria on thinking capacity, 12/14 criteria on leadership capacity and 3/7 criteria on financial management capacity had significant improvements after the intervention (p < 0.001). The average score of most of these criteria increased from about 3 points at the baseline to 4 points after the intervention. However, financial management capacity is the skill group with the least improvement among the 5 skill groups evaluated, the highest criterion only reaching an average of 4.07 points; this requires the need to continue to prioritize training for this content in the coming time.Conclution: There has been an improvement in hospital treatment and care outcomes following a series of capacity building training courses for head nurses.
Keywords: Năng lực quản lý; điều dưỡng trưởng khoa; hiệu quả; bệnh viện.